A validated liquid chromatography/tandem mass spectrometry method for the analysis of efavirenz in 0.2 mg hair samples from human immunodeficiency virus infected patients. (26th March 2018) - Johnston, Jenna; Orrell, Catherine; Smith, Peter; Joubert, Anton; Wiesner, Lubbe
Abstract : Rationale: Drug levels in hair provide a longer window of detection, compared to plasma drug levels, and therefore hair analysis has the advantage of assessing adherence over a longer period of time. No methods for the analysis of antiretroviral drugs in hair currently exist in South Africa, and worldwide there is only one validated method for the determination of efavirenz in hair that has been published. Methods: Efavirenz was extracted from 0.2 mg of hair through a simultaneous pulverization and extraction step. Separation was achieved on an Agilent Poroshell C18 column using an isocratic elution with a total run time of 3 min. A triple quadrupole mass spectrometer set to electrospray ionization in positive multiple reaction monitoring mode was used for detection. The method was validated over the concentration range 0.625–40 ng/mg. Results: Using ten times less hair than in a previously published method, the lower limit of quantitation was validated at 0.625 ng/mg. The interday and intraday assay precision, expressed as the percentage coefficient of variation (CV), for spiked calibration standards and quality control samples was lower than 7% and accuracy ranged from 97 to 110%. For quality controls prepared from authentic hair the CV was less than 12%. The extraction efficiency for authentic quality control samples was determined to be 83% after repeated extractions of the same samples. Conclusions: This paper reports the first quantitative method for the determination of efavirenz in hair to be developed in South Africa. The validated method allowed for the successful monitoring of efavirenz in hair collected from HIV‐infected patients as part of a clinical study.